IMPLEMENTATION POLICY OF BPBD OF THE REGENT OF ACEH SINGKIL NUMBER 14 OF 2025 DUTIES AND FUNCTIONS IN DISASTER RISK REDUCTION IN ACEH SINGKIL REGENCY - Syukri; Andri (RADJA PUBLIKA, 2026)
This study aims to determine and describe the implementation policy of the Regional Disaster Management Agency (BPBD) of the Aceh Singkil Regent Number 14 of 2025 Duties and Functions in Disaster Risk Reduction in Aceh Singkil Regency. used. This study uses a descriptive qualitative method with data collection techniques namely interviews, documentation and non-participant observation. Through purposive sampling techniques obtained two key informants consisting of the Head of the BPBD Service then several community opinions. The results of field research show that the cause of frequent regional flooding in Aceh Singkil Regency is several technical problems that have not been resolved properly such as Technical and Infrastructure Problems, Spatial Planning Problems, Social and Compliance Problems, Government Coordination Problems and Funding and Political Limitations. So that these disasters are not resolved because several problems from the government itself have not been resolved by the Aceh Singkil Regent. If the problems from the government have been resolved properly, I as a researcher believe that the problem of flooding can be resolved effectively and efficiently.